Reduced Immune Response to Inactivated Severe Acute Respiratory Syndrome Coronavirus 2 Vaccine in a Cohort of Immunocompromised Patients in Chile. (7th March 2022) - Balcells, M Elvira; Le Corre, Nicole; Durán, Josefina; Ceballos, María Elena; Vizcaya, Cecilia; Mondaca, Sebastián; Dib, Martín; Rabagliati, Ricardo; Sarmiento, Mauricio; Burgos, Paula I; Espinoza, Manuel; Ferrés, Marcela; et al.
Abstract: Background: Inactivated severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) vaccines have been widely implemented in low- and middle-income countries. However, immunogenicity in immunocompromised patients has not been established. Herein, we aimed to evaluate immune response to CoronaVac vaccine in these patients. Methods: This prospective cohort study included 193 participants with 5 different immunocompromising conditions and 67 controls, receiving 2 doses of CoronaVac 8–12 weeks before enrollment. The study was conducted between May and August 2021, at Red de Salud UC-CHRISTUS, Santiago, Chile. Neutralizing antibody (NAb) positivity, total anti–SARS-CoV-2 immunoglobulin G antibody (TAb) concentrations, and T-cell responses were determined. Results: NAb positivity and median neutralizing activity were 83.1% and 51.2% for the control group versus 20.6% and 5.7% (both P  < .001) in the solid organ transplant group, 41.5% and 19.2% (both P  < .0001) in the autoimmune rheumatic diseases group, 43.3% ( P  < .001) and 21.4% ( P <.01 or P  = .001) in the cancer with solid tumors group, 45.5% and 28.7% (both P  < .001) in the human immunodeficiency virus (HIV) infection group, 64.3% and 56.6% (both differences not significant) in the hematopoietic stem cell transplant group, respectively. TAb seropositivity was also lower for the solid organ transplant (20.6%; P  < .0001), rheumatic diseases (61%; P  < .001), and HIV groups (70.9%; P  = .003), compared with the control group (92.3%). On the other hand, the number of interferon γ spot-forming T cells specific for SARS-CoV-2 tended to be lower in all immunocompromising conditions but did not differ significantly between groups. Conclusions: Diverse immunocompromising conditions markedly reduce the humoral response to CoronaVac vaccine. These findings suggest that a boosting vaccination strategy should be considered in these vulnerable patients. Clinical Trials Registration: NCT04888793. Abstract : We assessed the immune response to a severe acute respiratory syndrome coronavirus-2 vaccine in immunocompromised patients. Humoral response in these patients was markedly reduced versus controls. We propose alternative vaccination schemes and/or the application of vaccine boosters in these patients..